2018
DOI: 10.1002/ijc.31238
|View full text |Cite
|
Sign up to set email alerts
|

RhoA‐stimulated intra‐capillary morphology switch facilitates the arrest of individual circulating tumor cells

Abstract: Metastasis is the primary cause of death for most cancer patients. Hematogenous arrest of circulating tumor cells (CTCs) is an essential prerequisite for metastases formation. Using transparent transgenic zebrafish (kdrl:eGFP; Casper), together with resonant laser scanning confocal microscopy, we tracked the fate of CTCs in vivo in the blood circulation for days. We found the intra-capillary morphology-switch (ICMS) of individual CTCs from strip to sphere was necessary for their intravascular arrests. Further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…This was a major breakthrough that highlighted a rather unappreciated role for RhoA in liver tumorigenesis in regards to several previous contradictory in vitro studies [99][100][101][102], underscoring the importance of in vivo models to better understand the role of RhoA signaling in health and disease. Further evidence revealed by Xi Huang and his colleagues linked RhoA activation to the arrest of circulating tumor cells in vivo [103]. Altogether, RhoA stimulation might represent a mechanism for reducing liver tumorigenesis and for halting the circulation of tumor cells in hematogenous metastatic disease.…”
Section: Rhoa In Pathology and Regenerationmentioning
confidence: 94%
“…This was a major breakthrough that highlighted a rather unappreciated role for RhoA in liver tumorigenesis in regards to several previous contradictory in vitro studies [99][100][101][102], underscoring the importance of in vivo models to better understand the role of RhoA signaling in health and disease. Further evidence revealed by Xi Huang and his colleagues linked RhoA activation to the arrest of circulating tumor cells in vivo [103]. Altogether, RhoA stimulation might represent a mechanism for reducing liver tumorigenesis and for halting the circulation of tumor cells in hematogenous metastatic disease.…”
Section: Rhoa In Pathology and Regenerationmentioning
confidence: 94%
“…This cellular rounding facilitated the entrapment of CTCs and their subsequent extravasation. 25 Accordingly, treatment with the ROCK inhibitor fasudil decreased the arrest of individual CTCs and the incidence of tumour metastasis in mice. Moreover, treatment with the myosin II inhibitor blebbistatin over a short period of time (3-6 h) delayed the formation of metastasis and the number of foci.…”
Section: Cytoplasmic Deformationmentioning
confidence: 99%
“…16 Other factors, such as the adhesion potential of CTCs, 17 the local blood pressure of the organ, its blood flow and the cell deformability, can also influence whether CTCs become arrested. 16,25 Indeed, Follain et al 16 demonstrated in vivo that low blood flow profiles can promote cell arrest without the need for the cells to be physically occluded, suggesting that active adhesion between CTCs and the endothelium is required for a successful extravasation. Other factors, such as the adhesion potential of CTCs 17 and the mechanical constraints of the capillary, 3,16 may also determine CTC arrest.…”
Section: Arrest In Capillaries and Mechanical Deformationmentioning
confidence: 99%
See 2 more Smart Citations